Qubits based mutual authentication protocol. Issue 3 (9th January 2022) - Nema, Prashant; Nene, Manisha J.
Abstract: Authentication of the entity is the initial step toward secure transaction over the internet. The evolution in the nature and types of attacks have forced the commerce industry to move from single factor to multi‐factor authentication technique largely employing biometric codes for human based entity. These biometric codes are unique and therefore, are synonymous to a user identity in the digital world. Hence, safeguarding the Biometric data becomes important for the user. Also, the classical authentication techniques relying on public key encryption schemes are no longer considered safe in the post quantum era. The research in this paper therefore, proposes a quantum based mutual authentication user‐server protocol which employs the principles of quantum mechanics to carry out secure exchange and storage of confidential data. The mathematical formulae validated through demonstration of properties of quantum mechanics verifies the ability of the protocol to work in compromised channel. The detailed security analysis carried out further quantifies the same and builds in confidence to adopt the quantum based mutual authentication protocol for critical user‐server data exchange.